The Nigerian Correctional Service (NCoS): Challenges and Opportunities in Deradicalization and Reintegration - Badrudeen Adesina Balogun; Mufutau Olusola Bello (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article examines the role of the Nigerian Correctional Service (NCoS) in deradicalization programs in Nigeria. Its objectives are to analyze the programs and services provided by NCoS, identify the challenges encountered, and evaluate NCoS’s efforts in safeguarding the human rights of program participants. The study adopts a qualitative approach with a case study design. Data were collected through literature reviews, interviews with NCoS officers, program participants, and community leaders, as well as observations in several correctional facilities. The findings reveal that NCoS has developed comprehensive deradicalization programs but faces significant challenges, including overcrowding in correctional facilities, limited funding, and a shortage of professional staff. While NCoS has made efforts to protect the human rights of program participants, stigma and discrimination remain substantial hurdles. Community involvement in the reintegration of former extremists is also crucial, though it requires more effective strategies. This article provides recommendations to enhance the effectiveness of deradicalization programs in Nigeria. These include improving correctional facility capacity, developing programs and curricula, enhancing the competence of personnel, and strengthening monitoring and evaluation systems.